Hubungan Antara Keputusan Memilih Restoran Fast Food dan Frekuensi Konsumsi Fast Food Terhadap Status Gizi Anak Sekolah Dasar - , TIANI KUSHARDIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Nowadays, nutritional problems that occur in developed countries and developing not only malnutrition but also more nutritional problems. Some research suggests that the causes of obesity are multifactorial, among others due to genetic factors, race, dietary changes, physical activity and psychological factors. Today's lifestyle can also lead to obesity which is the tendency to eat foods like modern fast food such as burgers, pizza, french fries and other high-fat and high calories but less fiber, vitamins and minerals. Objective : To determine the decision making of choosing a fast food restaurant and frequency of fast food associated with nutritional status. Method : This research is an observational cross-sectional design. The study was conducted in SD Negeri Pujokusuman 1 Yogyakarta. The study sample was 65 students. Respondents were selected using random sampling techniques. Bivariate analysis was employed by using chi-square test. Result : The study result that 63% of students rarely eat fast food (1-4x/month), 32% of students never eat fast food (<1x/month), and 4.6% of students frequently eat fast food (> 4x/month). Rational based decision making are 89% of students and social based decision making are 10.77%. The results of analysis of this study shows that there is no relationship between the decision making of choosing fast food restaurants with nutritional status (p> 0.05), there was no association between the frequency of fast food consumption and nutritional status (p> 0.05), and no relationship between decision making of choosing fast food restaurant with a frequency of fast food (p> 0.05). Conclusion : There is no relationship between the decision making of choosing fast food restaurant and the frequency of fast food and nutritional status on elementary school students.